Flame-retardant in-situ curing gel solid electrolyte with self-repairing function and preparation method thereof
By using in-situ polymerization method to form a flame-retardant in-situ solid gel electrolyte during the assembly process of lithium-ion batteries, the problem of intimate contact between the gel matrix and the active substance in the traditional method is solved, the conductivity and safety of the battery are improved, and the growth of lithium dendrites is inhibited through self-healing ability.
Patent Information
- Application Number
- CN202510099506.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-22
AI Technical Summary
When the traditional non-in-situ polymerization method forms gel solid electrolytes in lithium-ion batteries, the contact between the gel matrix and the surface of the active substance is not tight, resulting in large internal resistance of the interface, reducing the electrolyte conductivity and the comprehensive electrical performance of lithium-ion batteries.
In-situ polymerization is used to form a flame-retardant in-situ cured gel solid electrolyte during the assembly of lithium-ion batteries. By polymerizing and cross-linking the flame-retardant in-situ cured gel solid electrolyte under heating conditions, a semi-solid gel product is formed. The electrolyte consists of a lithium salt, a non-aqueous organic solvent, a gel polymer monomer and an initiator. The gel polymer monomer is composed of a flame retardant monomer, a crosslinked monomer and a self-healing monomer, and has a P-F chemical bond, a cyclotriphosphate group and a Si-O-Si chemical bond.
The interface internal resistance between the flame-retardant in-situ curing gel solid electrolyte formed by in-situ polymerization and the electrode active material is small, and the conductivity of the electrolyte does not decrease, which improves the conductivity and capacity retention of the lithium-ion battery, while enhancing the safety of the battery, and inhibits the growth of lithium dendrites through the self-healing ability of Si-O-Si chemical bonds.
Smart Images

Figure CN119812459A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a flame retardant in-situ curing gel solid electrolyte with a self-repairing function and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have long cycle life and high energy density, and are widely used in mobile electronic devices and large energy storage devices. However, traditional liquid electrolytes can hardly meet the needs of lithium-ion batteries to further develop in the direction of safety and high energy density. In comparison, the unique semi-solid properties of gel solid electrolytes can avoid the leakage of organic liquids and inhibit the growth of lithium dendrites, thereby improving the safety performance of batteries.
[0003] The non-in-situ polymerization of gel solid electrolyte usually prepares the gel solid electrolyte matrix externally, and then drips the electrolyte into it during the battery assembly process to form a gel solid electrolyte. However, this method is difficult to achieve close contact between the gel matrix and the surface of the active material. The interface internal resistance between the electrolyte and the electrode active material is large, which will significantly reduce the comprehensive electrical performance of the lithium-ion battery, such as the electrolyte conductivity and the specific capacity of the battery. Summary of the invention
[0004] The problem in the prior art is that a gel solid electrolyte is formed in the process of assembling lithium-ion batteries by non-in-situ polymerization, and the interface internal resistance between the gel solid electrolyte and the electrode active material is large, which will significantly reduce the electrolyte conductivity. In view of the above technical problems, the present invention provides a flame-retardant in-situ cured gel solid electrolyte with a self-repairing function, which is a semi-solid gel product obtained by polymerization and cross-linking of a flame-retardant in-situ cured gel solid electrolyte under heating conditions, wherein the flame-retardant in-situ cured gel solid electrolyte comprises a lithium salt, a non-aqueous organic solvent, a gel polymerization monomer and an initiator, wherein the gel polymerization monomer is composed of a flame-retardant monomer, a cross-linking monomer and a self-repairing monomer in a molar ratio of 0.1-2:1:0.1-2, wherein the flame-retardant monomer structure has a PF chemical bond and a cyclotriphosphonitrile group, and the self-repairing monomer structure has a Si-O-Si chemical bond.
[0005] Preferably, the non-aqueous organic solvent includes one or more of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), γ-butyrolactone (BC), methyl acetate (MA), ethyl acetate (EA), ethyl propionate (EP) and propyl propionate (PP).
[0006] Preferably, the lithium salt includes one or more of lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiODFB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0007] Preferably, the flame retardant monomer includes one or more of 2,4-bisbutenyloxytetrafluorocyclotriphosphazene, 2,4,6-tributenyloxytrifluorocyclotriphosphazene, 3-propyleneoxypentafluorocyclotriphosphazene, 2,4-bispropyleneoxytetrafluorocyclotriphosphazene, 2,4,6-tripropyleneoxytrifluorocyclotriphosphazene, 3-vinyloxypentafluorocyclotriphosphazene, 2,4-bisvinyloxytetrafluorocyclotriphosphazene, and 3-butenyloxypentafluorocyclotriphosphazene.
[0008] Among them, the structural formula of 3-butenyloxypentafluorocyclotriphosphazene is as follows:
[0009]
[0010] The structural formula of 2,4-bisbutenyloxytetrafluorocyclotriphosphazene is as follows:
[0011]
[0012] The structural formula of 2,4,6-tributenyloxy trifluorocyclotriphosphazene is as follows:
[0013]
[0014] The structural formula of 3-propyleneoxypentafluorocyclotriphosphazene is as follows:
[0015]
[0016] The structural formula of 2,4-bis(propyleneoxytetrafluorocyclotriphosphazene is as follows:
[0017]
[0018] The structural formula of 2,4,6-tripropyleneoxy trifluorocyclotriphosphazene is as follows:
[0019] The structural formula of 3-vinyloxypentafluorocyclotriphosphazene is as follows:
[0020] The structural formula of 2,4-bisvinyloxytetrafluorocyclotriphosphazene is as follows:
[0021]
[0022] The structural formula of 2,4,6-trivinyloxy trifluorocyclotriphosphazene is as follows:
[0023]
[0024] Preferably, the cross-linking monomer comprises N,N'-methylenebisacrylamide.
[0025] Preferably, the self-healing monomer includes one or more of tetramethyldivinyldisiloxane, vinyl-terminated dimethylpolysiloxane, tri(vinyldimethylsiloxy)phenylsilane, and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane.
[0026] Preferably, the initiator includes one or more of azobisisobutyronitrile, benzoyl peroxide, azobisisoheptanenitrile, and dimethyl azobisisobutyrate.
[0027] Preferably, the concentration of the lithium salt in the basic electrolyte is 0.5-2 mol / L.
[0028] Preferably, the added amount of the initiator accounts for 0.1-0.2% of the total mass of the flame-retardant in-situ cured gel solid electrolyte.
[0029] Preferably, the amount of the gel polymerized monomer added accounts for 1-25% of the total mass of the flame retardant in-situ cured gel solid electrolyte. The present invention has the following beneficial effects:
[0030] (1) The present invention adopts an in-situ polymerization method to form a flame-retardant in-situ cured gel solid electrolyte during the lithium ion battery assembly process. The interface internal resistance between the gel solid electrolyte and the electrode active material is small, which will not reduce the electrolyte conductivity, and is conducive to improving the conductivity and capacity retention rate of the lithium ion battery;
[0031] (2) The present invention has found that the composition of the polymerized monomers has a significant effect on the conductivity of the flame-retardant in-situ cured gel solid electrolyte obtained. The conductivity of the flame-retardant in-situ cured gel solid electrolyte obtained with different compositions of the polymerized monomers is significantly different, which in turn affects the various properties of the lithium-ion battery.
[0032] (3) The flame-retardant in-situ cured gel solid electrolyte obtained by the present invention uses a flame-retardant polymer monomer in the preparation process, which can further improve the safety of lithium-ion batteries;
[0033] (4) The flame-retardant in-situ cured gel solid electrolyte obtained by the present invention has Si-O-Si chemical bonds. The unique dynamic balance of the Si-O-Si chemical bonds gives the gel solid electrolyte good self-healing ability, which can effectively inhibit the growth of lithium dendrites. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1: Optical photographs of the flame retardant in-situ cured gel solid electrolyte obtained in Examples 1-3 respectively, and the morphology of the flame retardant in-situ cured gel solid electrolyte obtained after heating and curing.
[0035] Figure 2 : Graph showing the flame retardant performance test results of the flame retardant in-situ cured gel solid electrolyte obtained in Example 1.
[0036] Figure 3 : Conductivity test results of the flame-retardant in-situ cured gel solid electrolyte obtained in Examples 1-3 respectively. DETAILED DESCRIPTION
[0037] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0038] The main manufacturing process parameters of the CR2032 button battery to be filled in the present invention are as follows:
[0039] The positive electrode sheet of the CR2032 button battery is: the positive electrode active material (nickel cobalt manganese oxide lithium ternary positive electrode NCM811-S800, purchased from Ningbo Rongbai New Energy Technology Co., Ltd.), conductive carbon black (Ketjen Black EC-300J, Lion of Japan), polyvinylidene fluoride PVDF (Arkema of France) are mixed in a mass ratio of 96:2:2, and then an appropriate amount of N-methylpyrrolidone (NMP) is added to obtain a positive electrode slurry with a solid content of 65%. The positive electrode slurry is then evenly coated on both sides of the aluminum foil, and the double-sided coating surface density is 28 mg / cm 2 , compacted density is 3.4g / cm 3 , the double-sided coating thickness is 97μm, the aluminum foil thickness is 15μm, and the positive electrode sheet is cut into 14mm discs.
[0040] The negative electrode of the CR2032 button battery is lithium metal (Tianjin Zhongneng Lithium Industry Co., Ltd., metal lithium disc with a diameter of 16 mm and a thickness of 0.1 mm).
[0041] The separator model of the CR2032 button battery is Celgard 2325, 25 μm, purchased from Celgard Company in the United States.
[0042] The test method of conductivity in the present invention is as follows:
[0043] Ionic conductivity was measured by electrochemical impedance spectroscopy (EIS) using a Metrohm Autolab electrochemical workstation. A potential of ±10 mV was applied to a stainless steel (SS) symmetrical cell in the frequency range of 0.1 Hz to 1 MHz. Ionic conductivity can be calculated by the following formula:
[0044]
[0045] Where: I is the film thickness, Rb is the body resistance, and A is the area.
[0046] Example 1
[0047] A method for preparing a flame retardant in-situ curing gel solid electrolyte is as follows:
[0048] (1) adding 1 mol of LiPF6 to a non-aqueous organic solvent to obtain a basic electrolyte, wherein the non-aqueous organic solvent is composed of DEC, EC and EMC in a volume ratio of 2:3:5, and the concentration of LiPF6 in the basic electrolyte is 1 mol / L;
[0049] (2) Then, gel polymerization monomer and azobisisobutyronitrile are added to the basic electrolyte, and the mixture is stirred and dispersed uniformly to obtain a flame retardant in situ cured gel solid electrolyte. The gel polymerization monomer is composed of 3-butenyloxypentafluorocyclotriphosphazene (Suzhou Yaco Technology Co., Ltd., Article No. D0519), N,N'-methylenebisacrylamide, and tetramethyldivinyldisiloxane in a molar ratio of 1:1:1. The total weight of the gel polymerization monomer accounts for 3% of the total mass of the flame retardant in situ cured gel solid electrolyte, the amount of azobisisobutyronitrile added accounts for 0.5% of the total mass of the flame retardant in situ cured gel solid electrolyte, and the basic electrolyte accounts for 96.5% of the total mass of the flame retardant in situ cured gel solid electrolyte.
[0050] Example 2 is the same as Example 1, except that in Example 2, the total weight of the gel polymerized monomers accounts for 7% of the total mass of the flame-retardant in-situ cured gel solid electrolyte.
[0051] Example 3 is the same as Example 1, except that in Example 3, the total weight of the gel polymerized monomers accounts for 10% of the total mass of the flame-retardant in-situ cured gel solid electrolyte.
[0052] The optical photographs of the flame-retardant in-situ cured gel solid electrolyte obtained in Examples 1-3 and the morphology of the flame-retardant in-situ cured gel solid electrolyte obtained after heating and curing are shown in the attached manual. Figure 1 The flame retardant in-situ cured gel solid electrolyte obtained in Examples 1-3 was cured to form a flame retardant in-situ cured gel solid electrolyte. The specific test results are shown in the attached manual. Figure 3 As shown. As the proportion of gel polymer monomers in the flame-retardant in-situ cured gel solid electrolyte increases, the conductivity decreases from 0.556mS / cm to 0.24mS / cm. The flame retardant properties of the flame-retardant in-situ cured gel solid electrolyte obtained in Example 1 are shown in the attached manual. Figure 2 shown.
[0053] Example 4
[0054] A method for preparing a flame retardant in-situ curing gel solid electrolyte is as follows:
[0055] (1) adding 1.1 mol LiPF6 into a non-aqueous organic solvent to obtain a basic electrolyte, wherein the non-aqueous organic solvent is composed of EC and EMC in a volume ratio of 3:7, and the concentration of LiPF6 in the basic electrolyte is 1.1 mol / L;
[0056] (2) Then, gel polymerization monomer and azobisisobutyronitrile are added to the basic electrolyte, and the mixture is stirred and dispersed uniformly to obtain a flame retardant in situ cured gel solid electrolyte. The gel polymerization monomer is composed of 3-butenyloxypentafluorocyclotriphosphazene (Suzhou Yaco Technology Co., Ltd., D0519), N,N'-methylenebisacrylamide, and vinyl terminated dimethylpolysiloxane (CAS: 68083-19-2) in a molar ratio of 1.1:1:0.5. The total weight of the gel polymerization monomer accounts for 8% of the total mass of the flame retardant in situ cured gel solid electrolyte, the amount of azobisisobutyronitrile added accounts for 0.6% of the total mass of the flame retardant in situ cured gel solid electrolyte, and the basic electrolyte accounts for 91.4% of the total mass of the flame retardant in situ cured gel solid electrolyte.
[0057] Example 5
[0058] A method for preparing a flame retardant in-situ curing gel solid electrolyte is as follows:
[0059] (1) adding 1.2 mol LiPF6 into a non-aqueous organic solvent to obtain a basic electrolyte, wherein the non-aqueous organic solvent is composed of PC, EC and EMC in a volume ratio of 2:3:5, and the concentration of LiPF6 in the basic electrolyte is 1.2 mol / L;
[0060] (2) Then, gel polymerization monomer and azobisisobutyronitrile are added to the basic electrolyte, and the mixture is stirred and dispersed uniformly to obtain a flame retardant in situ cured gel solid electrolyte. The gel polymerization monomer is composed of 3-butenyloxypentafluorocyclotriphosphazene, N,N'-methylenebisacrylamide, and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane in a molar ratio of 0.5:1:0.4. The total weight of the gel polymerization monomer accounts for 10% of the total mass of the flame retardant in situ cured gel solid electrolyte, the amount of azobisisobutyronitrile added accounts for 0.7% of the total mass of the flame retardant in situ cured gel solid electrolyte, and the basic electrolyte accounts for 89.3% of the total mass of the flame retardant in situ cured gel solid electrolyte.
[0061] Example 6
[0062] A method for preparing a flame retardant in-situ curing gel solid electrolyte is as follows:
[0063] (1) adding 1 mol of LiPF6 into a non-aqueous organic solvent to obtain a basic electrolyte, wherein the non-aqueous organic solvent is composed of EC and DMC in a volume ratio of 2:8, and the concentration of LiPF6 in the basic electrolyte is 1 mol / L;
[0064] (2) Then, gel polymerization monomer and azobisisobutyronitrile are added to the basic electrolyte, and the mixture is stirred and dispersed uniformly to obtain a flame retardant in situ cured gel solid electrolyte. The gel polymerization monomer is composed of 3-butenyloxypentafluorocyclotriphosphazene (Suzhou Yaco Technology Co., Ltd., D0519), N,N'-methylenebisacrylamide, and tris(vinyldimethylsiloxy)phenylsilane in a molar ratio of 0.6:1:0.5. The total weight of the gel polymerization monomer accounts for 4% of the total mass of the flame retardant in situ cured gel solid electrolyte, the amount of azobisisobutyronitrile added accounts for 0.4% of the total mass of the flame retardant in situ cured gel solid electrolyte, and the basic electrolyte accounts for 95.6% of the total mass of the flame retardant in situ cured gel solid electrolyte.
[0065] Example 7
[0066] A method for preparing a flame retardant in-situ curing gel solid electrolyte is as follows:
[0067] (1) adding 1.1 mol LiPF6 into a non-aqueous organic solvent to obtain a basic electrolyte, wherein the non-aqueous organic solvent is composed of EC and DEC in a volume ratio of 4:6, and the concentration of LiPF6 in the basic electrolyte is 1.1 mol / L;
[0068] (2) Then, gel polymerization monomer and azobisisobutyronitrile are added to the basic electrolyte, and the mixture is stirred and dispersed uniformly to obtain a flame retardant in situ cured gel solid electrolyte. The gel polymerization monomer is composed of 3-butenyloxypentafluorocyclotriphosphazene, N,N'-methylenebisacrylamide, and tri(vinyldimethylsilyloxy)phenylsilane in a molar ratio of 0.6:1:0.9, and the total weight of the gel polymerization monomer accounts for 4% of the total mass of the flame retardant in situ cured gel solid electrolyte. The amount of azobisisobutyronitrile added accounts for 0.4% of the total mass of the flame retardant in situ cured gel solid electrolyte, and the basic electrolyte accounts for 95.6% of the total mass of the flame retardant in situ cured gel solid electrolyte.
[0069] Example 8
[0070] A method for preparing a flame retardant in-situ curing gel solid electrolyte is as follows:
[0071] (1) adding 1.2 mol LiPF6 into a non-aqueous organic solvent to obtain a basic electrolyte, wherein the non-aqueous organic solvent is composed of EC, DEC, and FEC in a volume ratio of 3:3:4, and the concentration of LiPF6 in the basic electrolyte is 1.2 mol / L;
[0072] (2) Then, gel polymerization monomer and azobisisobutyronitrile are added to the basic electrolyte, and the mixture is stirred and dispersed uniformly to obtain a flame retardant in situ cured gel solid electrolyte. The gel polymerization monomer is composed of 3-butenyloxypentafluorocyclotriphosphazene, N,N'-methylenebisacrylamide, and tri(vinyldimethylsilyloxy)phenylsilane in a molar ratio of 0.5:1:0.7, and the total weight of the gel polymerization monomer accounts for 8% of the total mass of the flame retardant in situ cured gel solid electrolyte. The amount of azobisisobutyronitrile added accounts for 0.8% of the total mass of the flame retardant in situ cured gel solid electrolyte, and the basic electrolyte accounts for 91.2% of the total mass of the flame retardant in situ cured gel solid electrolyte.
[0073] Comparative Example 1 is the same as Example 4, except that the gel polymerization monomer in Comparative Example 1 is composed of 3-butenyloxypentafluorocyclotriphosphazene, N,N'-methylenebisacrylamide, and vinyl-terminated dimethylpolysiloxane in a molar ratio of 0.05:1:0.5.
[0074] Comparative Example 2 is the same as Example 4, except that the gel polymerization monomer in Comparative Example 2 is composed of 3-butenyloxypentafluorocyclotriphosphazene, N,N'-methylenebisacrylamide, and vinyl-terminated dimethylpolysiloxane in a molar ratio of 1.1:1:0.
[0075] Comparative Example 3 is the same as Example 4, except that the gel polymerization monomer in Comparative Example 3 is composed of 3-butenyloxypentafluorocyclotriphosphazene, N,N'-methylenebisacrylamide, and vinyl-terminated dimethylpolysiloxane in a molar ratio of 3:1:1.
[0076] Comparative Example 4 is the same as Example 4, except that the gel polymerization monomer in Comparative Example 4 is composed of 3-butenyloxypentafluorocyclotriphosphazene, N,N'-methylenebisacrylamide, and vinyl-terminated dimethylpolysiloxane in a molar ratio of 1.1:1:3.
[0077] Comparative Example 5 is the same as Example 4, except that in Comparative Example 5, the total weight of the gel polymerized monomers accounts for 30% of the total weight of the flame-retardant in-situ cured gel solid electrolyte.
[0078] Performance Testing
[0079] The optical photographs of the flame-retardant in-situ cured gel solid electrolyte and electrolyte obtained in Examples 1-3 are as shown in the attached manual. Figure 1 shown.
[0080] The combustion conditions of the flame-retardant in-situ cured gel solid electrolyte obtained in Example 1 after ignition are shown in the attached manual. Figure 2 shown.
[0081] The flame-retardant in-situ cured gel solid electrolyte obtained in Examples 1-3 was respectively injected into the steel shell of the CR2032 button battery to be filled, and the electrolyte was heated in situ (60°C) in the steel shell to cure to form a flame-retardant in-situ cured gel solid electrolyte. After the battery was subsequently packaged, three different button batteries were obtained.
[0082] Under the same test conditions, the impedance test was performed on the button batteries obtained in Examples 1-3. The test results are shown in the attached specification. Figure 3 As shown, the test results show that with the increase of the proportion of gel polymer monomers in the flame-retardant in-situ cured gel solid electrolyte, the impedance of the button battery shows an increasing trend.
[0083] The flame retardant in-situ cured gel solid electrolyte obtained in Example 4 is cured by heating (60°C) to form a flame retardant in-situ cured gel solid electrolyte. After testing, the conductivity of the flame retardant in-situ cured gel solid electrolyte obtained in Example 4 is 1.03mS / cm.
[0084] The flame-retardant in-situ solidified gel electrolyte obtained in Example 4 was injected into the steel shell of the CR2032 button battery to be injected (the injection coefficient was 5g / Ah), and the electrolyte was heated in-situ (60°C) in the steel shell to solidify to form a flame-retardant in-situ solidified gel electrolyte. After the battery was subsequently packaged, a button battery was obtained. The 0.1C discharge specific capacity of the obtained button battery was 214mAh / g. The button battery obtained in Example 4 was subjected to a charge and discharge (1C charge, 1C discharge) cycle life test in the voltage range of 2.7-4.4V. The capacity retention rate of the button battery obtained in Example 4 after 100 charge and discharge cycle tests can still reach 91%.
[0085] The flame retardant in-situ cured gel solid electrolyte obtained in Example 5 is cured by heating (60°C) to form a flame retardant in-situ cured gel solid electrolyte. After testing, the conductivity of the flame retardant in-situ cured gel solid electrolyte obtained in Example 5 is 0.42mS / cm.
[0086] The flame-retardant in-situ solidified gel electrolyte obtained in Example 5 was injected into the steel shell of the CR2032 button battery to be injected (the injection coefficient was 5g / Ah), and the electrolyte was heated in-situ (60°C) in the steel shell to solidify to form a flame-retardant in-situ solidified gel electrolyte. After the battery was subsequently packaged, a button battery was obtained. The 0.1C discharge specific capacity of the obtained button battery was 202mAh / g. The button battery obtained in Example 5 was subjected to a charge and discharge (1C charge, 1C discharge) cycle life test in the voltage range of 2.7-4.4V. The test results showed that the capacity retention rate of the button battery obtained in Example 5 after 100 charge and discharge cycle tests could still reach 92%.
[0087] The flame retardant in-situ cured gel solid electrolyte obtained in Example 6 is cured by heating (60°C) to form a flame retardant in-situ cured gel solid electrolyte. After testing, the conductivity of the flame retardant in-situ cured gel solid electrolyte obtained in Example 6 is 0.39 mS / cm.
[0088] The flame-retardant in-situ solidified gel electrolyte obtained in Example 6 was injected into the steel shell of the CR2032 button battery to be injected (the injection coefficient was 5g / Ah), and the electrolyte was heated in-situ (60°C) in the steel shell to solidify to form a flame-retardant in-situ solidified gel electrolyte. After the battery was subsequently packaged, a button battery was obtained. The 0.1C discharge specific capacity of the obtained button battery was 197mAh / g. The button battery obtained in Example 6 was subjected to a charge and discharge (1C charge, 1C discharge) cycle life test in the voltage range of 2.7-4.4V. The test results showed that the capacity retention rate of the button battery obtained in Example 6 after 100 charge and discharge cycle tests could still reach 95%.
[0089] The flame retardant in-situ cured gel solid electrolyte obtained in Example 7 is cured by heating (60°C) to form a flame retardant in-situ cured gel solid electrolyte. After testing, the conductivity of the flame retardant in-situ cured gel solid electrolyte obtained in Example 7 is 0.48 mS / cm.
[0090] The flame-retardant in-situ solidified gel electrolyte obtained in Example 7 was injected into the steel shell of the CR2032 button battery to be injected (the injection coefficient was 5g / Ah), and the electrolyte was heated in-situ (60°C) in the steel shell to solidify to form a flame-retardant in-situ solidified gel electrolyte. After the battery was subsequently packaged, a button battery was obtained. The 0.1C discharge specific capacity of the obtained button battery was 203mAh / g. The button battery obtained in Example 7 was subjected to a charge and discharge (1C charge, 1C discharge) cycle life test in the voltage range of 2.7-4.4V. The test results showed that the capacity retention rate of the button battery obtained in Example 7 after 100 charge and discharge cycle tests could still reach 88.4%.
[0091] The flame retardant in-situ cured gel solid electrolyte obtained in Example 8 is cured by heating (60°C) to form a flame retardant in-situ cured gel solid electrolyte. After testing, the conductivity of the flame retardant in-situ cured gel solid electrolyte obtained in Example 8 is 0.40 mS / cm.
[0092] The flame-retardant in-situ solidified gel electrolyte obtained in Example 8 was injected into the steel shell of the CR2032 button battery to be injected (the injection coefficient was 5g / Ah), and the electrolyte was heated in-situ (60°C) in the steel shell to solidify to form a flame-retardant in-situ solidified gel electrolyte. After the battery was subsequently packaged, a button battery was obtained. The 0.1C discharge specific capacity of the obtained button battery was 199mAh / g. The button battery obtained in Example 8 was subjected to a charge and discharge (1C charge, 1C discharge) cycle life test in the voltage range of 2.7-4.4V. The test results showed that the capacity retention rate of the button battery obtained in Example 8 after 100 charge and discharge cycle tests could still reach 97.2%.
[0093] The flame retardant in-situ cured gel solid electrolyte obtained in Comparative Example 1 was cured by heating (60°C) to form a flame retardant in-situ cured gel solid electrolyte. After testing, the conductivity of the flame retardant in-situ cured gel solid electrolyte obtained in Comparative Example 1 was 0.08mS / cm.
[0094] The flame-retardant in-situ solidified gel electrolyte obtained in Comparative Example 1 was injected into the steel shell of the CR2032 button battery to be injected (the injection coefficient was 5g / Ah), and the electrolyte was heated in-situ (60°C) in the steel shell to solidify to form a flame-retardant in-situ solidified gel electrolyte. After the battery was subsequently packaged, a button battery was obtained. The 0.1C discharge specific capacity of the obtained button battery was 138.4mAh / g, and the capacity retention rate of the button battery obtained in Comparative Example 1 after 100 charge and discharge cycle tests could still reach 79%.
[0095] In addition, since the amount of 3-butenyloxypentafluorocyclotriphosphazene added in Comparative Example 1 is relatively small, the flame retardant test results show that although a gel solid electrolyte is formed, it does not have flame retardant properties.
[0096] The flame retardant in-situ cured gel solid electrolyte obtained in Comparative Example 2 was cured by heating (60°C) to form a flame retardant in-situ cured gel solid electrolyte. After testing, the conductivity of the flame retardant in-situ cured gel solid electrolyte obtained in Comparative Example 2 was 0.13 mS / cm.
[0097] The flame retardant in-situ solidified gel electrolyte obtained in comparative example 2 was injected into the steel shell of the CR2032 button battery to be injected (the injection coefficient was 5g / Ah), and the electrolyte was heated in-situ (60°C) in the steel shell to solidify to form a flame retardant in-situ solidified gel electrolyte. After the battery was subsequently packaged, a button battery was obtained. The 0.1C discharge specific capacity of the obtained button battery was 155mAh / g, and the capacity retention rate of the button battery obtained in comparative example 2 after 100 charge and discharge cycle tests was only 77%.
[0098] The flame retardant in-situ cured gel solid electrolyte obtained in Comparative Example 3 was cured by heating (60°C) to form a flame retardant in-situ cured gel solid electrolyte. After testing, the conductivity of the flame retardant in-situ cured gel solid electrolyte obtained in Comparative Example 3 was 0.032 mS / cm.
[0099] The flame-retardant in-situ solidified gel electrolyte obtained in Comparative Example 3 was injected into the steel shell of the CR2032 button battery to be injected (the injection coefficient was 5g / Ah), and the electrolyte was heated in-situ (60°C) in the steel shell to solidify to form a flame-retardant in-situ solidified gel electrolyte. After the battery was subsequently packaged, a button battery was obtained. The 0.1C discharge specific capacity of the obtained button battery was 98.4mAh / g, and the capacity retention rate of the button battery obtained in Comparative Example 3 after 100 charge and discharge cycle tests was only 62%.
[0100] The flame retardant in-situ cured gel solid electrolyte obtained in Comparative Example 4 was cured by heating (60°C) to form a flame retardant in-situ cured gel solid electrolyte. After testing, the conductivity of the flame retardant in-situ cured gel solid electrolyte obtained in Comparative Example 4 was 0.12mS / cm.
[0101] The flame-retardant in-situ solidified gel electrolyte obtained in Comparative Example 4 was injected into the steel shell of the CR2032 button battery to be injected (the injection coefficient was 5g / Ah), and the electrolyte was heated in-situ (60°C) in the steel shell to solidify to form a flame-retardant in-situ solidified gel electrolyte. After the battery was subsequently packaged, a button battery was obtained. The 0.1C discharge specific capacity of the obtained button battery was 112.8mAh / g, and the capacity retention rate of the button battery obtained in Comparative Example 4 after 100 charge and discharge cycle tests was only 58%.
[0102] The flame retardant in-situ cured gel solid electrolyte obtained in Comparative Example 5 is cured by heating (60°C) to form a flame retardant in-situ cured gel solid electrolyte. After testing, the conductivity of the flame retardant in-situ cured gel solid electrolyte obtained in Comparative Example 5 is 0.078mS / cm.
[0103] The flame retardant in-situ solidified gel electrolyte obtained in Comparative Example 5 was injected into the steel shell of the CR2032 button battery to be injected (the injection coefficient was 5g / Ah), and the electrolyte was heated in-situ (60°C) in the steel shell to solidify to form a flame retardant in-situ solidified gel electrolyte. After the battery was subsequently packaged, a button battery was obtained. The 0.1C discharge specific capacity of the obtained button battery was 102mAh / g, and the capacity retention rate of the button battery obtained in Comparative Example 5 after 100 charge and discharge cycle tests was only 68%.
[0104] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A flame-retardant in-situ curing gel solid electrolyte with self-repairing function, characterized in that: The invention relates to a semi-solid gel product obtained by polymerizing and cross-linking a flame-retardant in-situ cured gel solid electrolyte under heating conditions. The flame-retardant in-situ cured gel solid electrolyte comprises a basic electrolyte, a gel polymerization monomer and an initiator. The basic electrolyte is formed by mixing a lithium salt and a non-aqueous organic solvent. The gel polymerization monomer comprises a flame-retardant monomer, a cross-linking monomer and a self-healing monomer in a molar ratio of 0.1-2:1:0.1-2. The flame-retardant monomer structure has a PF chemical bond and a cyclotriphosphonitrile group, and the self-healing monomer structure has a Si-O-Si chemical bond.
2. The flame-retardant in-situ curing gel solid electrolyte with self-repairing function according to claim 1, characterized in that: The non-aqueous organic solvent includes one or more of EC, PC, EC, DMC, DEC, EMC, FEC, BC, MA, EA, EP and PP.
3. The flame-retardant in-situ curing gel solid electrolyte with self-repairing function according to claim 1, characterized in that: The lithium salt includes one or more of LiClO4, LiBF4, LiPF6, LiBOB, LiODFB, LiFSI, and LiTFSI.
4. The flame-retardant in-situ curing gel solid electrolyte with self-repairing function according to claim 1, characterized in that: The flame retardant monomer includes one or more of 3-butenyloxy pentafluorocyclotriphosphazene, 2,4-bis-butenyloxy tetrafluorocyclotriphosphazene, 2,4,6-tributenyloxy trifluorocyclotriphosphazene, 3-propyleneoxy pentafluorocyclotriphosphazene, 2,4-bis-propyleneoxy tetrafluorocyclotriphosphazene, 2,4,6-tri-propyleneoxy trifluorocyclotriphosphazene, 3-vinyloxy pentafluorocyclotriphosphazene, 2,4-bis-vinyloxy tetrafluorocyclotriphosphazene and 3-butenyloxy pentafluorocyclotriphosphazene.
5. The flame-retardant in-situ curing gel solid electrolyte with self-repairing function according to claim 1, characterized in that: The cross-linking monomer includes N,N'-methylenebisacrylamide.
6. The flame-retardant in-situ curing gel solid electrolyte with self-repairing function according to claim 1, characterized in that: The self-healing monomer includes one or more of tetramethyldivinyldisiloxane, vinyl-terminated dimethylpolysiloxane, tri(vinyldimethylsiloxy)phenylsilane, and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane.
7. The flame-retardant in-situ curing gel solid electrolyte with self-repairing function according to claim 1, characterized in that: The initiator includes one or more of azobisisobutyronitrile, benzoyl peroxide, azobisisoheptanenitrile and dimethyl azobisisobutyrate.
8. The flame-retardant in-situ curing gel solid electrolyte with self-repairing function according to claim 1, characterized in that: The concentration of lithium salt in the basic electrolyte is 0.5-2 mol / L.
9. The flame-retardant in-situ curing gel solid electrolyte with self-repairing function according to claim 1, characterized in that: The added amount of the initiator accounts for 0.1-0.2% of the total mass of the flame-retardant in-situ curing gel solid electrolyte.
10. The flame-retardant in-situ curing gel solid electrolyte with self-repairing function according to claim 1, characterized in that: The added amount of the gel polymerization monomer accounts for 1-25% of the total mass of the flame-retardant in-situ cured gel solid electrolyte.
Citation Information
Patent Citations
Non-combustible lithium-sulfur or sodium-sulfur cell electrolyte solution and preparation method therefor
CN105789683A
Benzimidazole-containing single-ion polymer electrolyte as well as preparation method and application thereof
CN114865071A
Flame-retardant electrolyte, preparation method thereof and lithium metal battery
CN115692835A
Electrolyte, preparation method thereof and lithium ion battery
CN116960461A
Gel electrolyte battery and preparation method thereof
CN117790886A